Respostas
respondido por:
3
x²-2x+3m=0
(-1)²-2.(-1)+3m=0
1+2+3m=0
3m+3=0
3m=-3
m=-3/3
m=-1
O valor de m=-1.
Boa noite!
ECS.16/12/2016
(-1)²-2.(-1)+3m=0
1+2+3m=0
3m+3=0
3m=-3
m=-3/3
m=-1
O valor de m=-1.
Boa noite!
ECS.16/12/2016
respondido por:
7
x² - 2 x + 3 m = 0
Δ = b² - 4 . a . c
b² - 4 . a . c = - 1
( - 2 )² - 4 . 1 . ( 3 m ) = - 1
4 - 12 m = - 1
12 m = 5
m = 5 / 12
Δ = b² - 4 . a . c
b² - 4 . a . c = - 1
( - 2 )² - 4 . 1 . ( 3 m ) = - 1
4 - 12 m = - 1
12 m = 5
m = 5 / 12
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás